The effects of psychological distance on spontaneous justice inferences: A construal level theory perspective - Zhang, Qing; Wei, Wei; Li, Ningchen; Cao, Wen (Frontiers in Psychology, 2022)
Objective The aim of this study was to examine the effects of psychological distance on spontaneous justice inferences. Methods Two experiments were conducted using the probe recognition paradigm to directly examine whether psychological distance affects spontaneous justice inferences. In Experiment 1, the spatial distance of justice actions from the perceivers was manipulated. In Experiment 2, temporal distance was manipulated. Results Consistent with our expectations, the results of Experiments 1 and 2 (for spatial distance and temporal distance, respectively) consistently demonstrated the effect of psychological distance on spontaneous justice inferences. In concrete terms, participants made stronger spontaneous justice inferences when confronted with situation descriptions of justice-implying events occurring in a spatially distant location than in a proximal location (Experiment 1) and in the distant-future condition than in the near-future condition (Experiment 2). Conclusion These findings indicate that psychological distance can influence influence simplicity, unintentional processing of justice inferences.